Comparative Characteristics of Surgical Methods for Fixing Bone Fragments of the Zygomatic Bone and Arch - Kamolova Feruza Rahmatilloyevna; Qalandarov Eldor Shermat ugli (Genius Journals, 2022)
The zygomatic arch is a complex formed by the temporal process of the zygomatic bone. Quite often, fractures of the zygomatic arch proper are observed, which do not extend to the body of the zygomatic bone and its other processes
Keywords: Zygomatic-orbital zone; zygomatic bone; trauma; bone defect